Myth in feminine gender and the (in)visibilisation of the body (Colloquia Comparativa Litterarum, 2025)
Brigitte Le Juez and Metka Zupančič (editors). Myth in Feminine Gender and the (In)Visibilisation of the Body. Leiden-Boston, Brill, 2021, 268 p.